Reformations : the early modern world, 1450-1650 - Eire, Carlos M. N. (New Haven ; London : Yale University Press, 2016)
"This fast-paced survey of Western civilization's transition from the Middle Ages to modernity brings that tumultuous period vividly to life. Carlos Eire, popular professor and gifted writer, chronicles the two-hundred-year era of the Renaissance and Reformation with particular attention to issues that persist as concerns in the present day. Eire connects the Protestant and Catholic Reformations in new and profound ways, and he demonstrates convincingly that this crucial turning point in history not only affected people long gone, but continues to shape our world and define who we are today. The book focuses on the vast changes that took place in Western civilization between 1450 and 1650, from Gutenberg's printing press and the subsequent revolution in the spread of ideas to the close of the Thirty Years' War. Eire devotes equal attention to the various Protestant traditions and churches as well as to Catholicism, skepticism, and secularism, and he takes into account the expansion of European culture and religion into other lands, particularly the Americas and Asia. He also underscores how changes in religion transformed the Western secular world. Created with students and nonspecialists in mind, Reformations is an inspiring, provocative volume for any reader who is curious about the role of ideas and beliefs in history."--Jacket.
Part one: On the edge. Rome, 1450 ; An age of breakthroughs ; Religion in late medieval Christendom ; Reform and dissent in the late Middle Ages ; Italian Humanism ; Humanism beyond Italy ; Forerunners of the Catholic Reformation -- Part two: Protestants. Rome, 1510 ; Luther : from student to monk ; Luther : from rebel to heretic ; Luther : the reactionary ; The Swiss Reformation ; The Radical Reformation ; Calvin and Calvinism ; England, Wales, Ireland, and Scotland, 1521-1603 -- Part three: Catholics. Rome, 1564 ; Catholic reform : facing the challenge ; Catholic reform : healing the body of Christ ; Catholic reform : fashioning a new clergy ; Catholic reform : the Society of Jesus ; Missions to the New World ; Missions to the East Indies -- Part four: Consequences. Rome, 1626 ; The age of religious wars ; The age of orthodoxy ; The confessional age ; The age of devils ; The age of reasonable doubt ; The age of outcomes ; The spirit of the age -- Epilogue: Assessing the reformations.
Includes bibliographical references (pages [759]-856) and index.
Keywords: Reformation; Counter-Reformation.; Renaissance